(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Because of their superior qualities and ability to be applied to a wide range of applications, fibre reinforced polymer composites are gradually displacing conventional materials. due to the fiber-reinforced material’s lower density than metals, which causes the composites’ better strength to weight ratio. Modern material advancement is playing a big role in the production of products across several industries. Many experts are searching for basic materials with high strength, low weight, and low cost. We prefer composite materials because they are lighter and more robust. The project’s goal is to develop camel hair and its hybrids through a manual lay-up technique that uses hardener and epoxy. Using the combinations listed above, the following glass powder concentrations can be used: Basalt+15%, Kenaf + 15%, Camel Hair + 15%, Basalt + Kenaf + 15%, Kenaf + Camel Hair + 15%, Camel hair + Basalt + 15%, and Basalt + Kenaf + Camel Hair+15%. Tensile, flexural, impact, and hardness tests were used to ascertain the qualities of these composites, which were then manufactured into crossover materials that are evaluated provisionally in accordance with ASTM standards. Whichever material works best was determined after utilising catia software to build the helmet and Ansys software to conduct a static analysis. Von-mises stress, total deformation, shear stress, and strain were noted.